Topics in sports economics - Miceli, Thomas J. (Cheltenham ; Northampton : Edward Elgar Publishing, 2025)
This innovative book examines key financial dimensions within the world of sports. Thomas J. Miceli discusses topics ranging from the business nature of sports leagues and the pricing of sports events to college sports and the implementation of sports–related public policies. Viewing sports leagues as competitive economic organizations, Miceli examines the unique aspects of the labour market for professional athletes. Utilising examples from the National Football League, Major League Baseball and the National Collegiate Athletic Association, he expands on athletes’ wages, exploring salary determination, risk sharing and incentives, as well as payment of college-level athletes and players training in the minor leagues. The book discusses the optimal enforcement of rules in sports and the level of punishment required to keep sports fair, evaluating policy issues such as the relationship between sports and gambling and discrimination.
Publikace se zaměřuje na ekonomické aspekty sportu a nabízí systematický přehled klíčových témat sportovní ekonomie. Autor nahlíží sportovní ligy jako specifické konkurenční ekonomické organizace a analyzuje jejich fungování z hlediska financování, tvorby cen sportovních událostí a struktury trhu. Zvláštní pozornost je věnována trhu práce profesionálních sportovců, včetně určování mezd, sdílení rizik, motivačních mechanismů a odměňování hráčů na univerzitní i nižší úrovni soutěží. Kniha se rovněž zabývá vymáháním pravidel ve sportu, otázkami spravedlnosti soutěží, vztahem sportu a hazardu, diskriminací a rolí veřejných politik v oblasti sportu.
Obsahuje bibliografické odkazy a rejstřík
Keywords: ekonomika sportu; sportovní management; profesionální sport; odměňování; financování sportu; monografie; sports economics; sports management; professional sports; compensation; monographs